2022
DOI: 10.3390/ijms23031606
|View full text |Cite
|
Sign up to set email alerts
|

SARM1 Ablation Is Protective and Preserves Spatial Vision in an In Vivo Mouse Model of Retinal Ganglion Cell Degeneration

Abstract: The challenge of developing gene therapies for genetic forms of blindness is heightened by the heterogeneity of these conditions. However, mechanistic commonalities indicate key pathways that may be targeted in a gene-independent approach. Mitochondrial dysfunction and axon degeneration are common features of many neurodegenerative conditions including retinal degenerations. Here we explore the neuroprotective effect afforded by the absence of sterile alpha and Toll/interleukin-1 receptor motif-containing 1 (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…So, how does this mitochondrial dysfunction induced by rotenone correlates with cell death? Our previous study and a few recent studies have indicated that the TLR adaptor protein sterile alpha and TIR motif containing 1 (Sarm1) play a pivotal role in this process as knockdown of Sarm1 showed a significant reduction in rotenone-induced cell death in SH-SY5Y cells [10,11]. Furthermore, a study by Hughes et al [12] has revealed that Sarm1 inhibition can prevent axonal Abbreviations DMEM, Dulbecco's modified Eagle's medium; LC3, light-chain 3; NAD + , nicotinamide adenine dinucleotide + ; NR, nicotinamide riboside; PD, Parkinson's disease; RFP, red fluorescent protein; ROS, reactive oxygen species; SRB, sulforhodamine B.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, how does this mitochondrial dysfunction induced by rotenone correlates with cell death? Our previous study and a few recent studies have indicated that the TLR adaptor protein sterile alpha and TIR motif containing 1 (Sarm1) play a pivotal role in this process as knockdown of Sarm1 showed a significant reduction in rotenone-induced cell death in SH-SY5Y cells [10,11]. Furthermore, a study by Hughes et al [12] has revealed that Sarm1 inhibition can prevent axonal Abbreviations DMEM, Dulbecco's modified Eagle's medium; LC3, light-chain 3; NAD + , nicotinamide adenine dinucleotide + ; NR, nicotinamide riboside; PD, Parkinson's disease; RFP, red fluorescent protein; ROS, reactive oxygen species; SRB, sulforhodamine B.…”
Section: Introductionmentioning
confidence: 99%
“…So, how does this mitochondrial dysfunction induced by rotenone correlates with cell death? Our previous study and a few recent studies have indicated that the TLR adaptor protein sterile alpha and TIR motif containing 1 (Sarm1) play a pivotal role in this process as knockdown of Sarm1 showed a significant reduction in rotenone‐induced cell death in SH‐SY5Y cells [10,11]. Furthermore, a study by Hughes et al.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of ophNdi1 and NDI1 to decrease ROS, a significant feature of mitochondrial dysfunction, and increase NADH oxidation activity, an indirect measure of complex I activity, was evaluated. To induce complex I deficiency and mitochondrial dysfunction, rotenone, a complex I inhibitor was utilised; an increase in ROS levels is typically a feature of rotenone-induced mitochondrial dysfunction [ 49 , 68 , 69 ]. Mitochondrial and cellular ROS levels were determined in ophNdi1 and NDI1 transfected HEK293 cells 24 h post-rotenone insult (5 nM) using MitoSOX™ and CellROX™ assays, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A mitochondrial stress test was performed 48 h later according to the manufacturer’s protocols (Seahorse XFe96 extracellular flux analyser, Agilent Technologies, CA, USA). Injection cycles were 5× for basal OCR, 5× following oligomycin (1 µM), 5× following FCCP (1 µM), 5× following rotenone (0.5 µM) and 5× following antimycin A (0.5 µM) injections [ 4 , 49 ]. Six replicas per group were analysed.…”
Section: Methodsmentioning
confidence: 99%
“…Overexpression of Nmnat1 in RGCs of D2 mice also prevented glaucomatous nerve damage in >70% of treated eyes ( Williams et al, 2017b ). On the other hand, suppression of SARM1 has been demonstrated to protect against mitochondrial dysfunction, leading to preservation of axon degeneration and retaining of visual function in an in vivo mouse model of RGC degeneration ( Finnegan et al, 2022 ).…”
Section: Genome Editing Of Glaucomamentioning
confidence: 99%